Neutrophil Gelatinase-Associated Lipocalin and Retinol-Binding Protein-4 as Biomarkers for Diabetic Kidney Disease - Fatemeh Abbasi; Fatemeh Moosaie; Pegah Khaloo; Fatemeh Dehghani Firouzabadi; Seyede Marzie Fatemi Abhari; Bahar Atainia; Maryam Ardeshir; Manouchehr Nakhjavani; Alireza Esteghamati (Karger Publishers, 2020)
Aims: This study was designed to evaluate the conflicting association between 2 tubular protein markers including neutrophil gelatinase-associated lipocalin (NGAL) and retinol-binding protein-4 (RBP-4) with albuminuria and glomerular filtration rate (GFR) and calculate the accuracy of the role of NGAL and RBP-4 in diagnosis of diabetic nephropathy (DN) in patients with type2 diabetes. Methods: This is a cross-sectional study that included 133 patients with type 2 diabetes. There were 3 diabetic study groups with normoalbuminuria, moderately increased albuminuria, severely increased albuminuria, and non-diabetic control group without any renal disease. We analyzed the difference of urinary NGAL (uNGAL) and RBP-4 between nondiabetics and diabetics, as well as within the diabetic group. We also assessed the association between albuminuria and NGAL and RBP-4. Results: The urinary levels of NGAL and RBP-4 were higher in patients with type 2 diabetes compared to nondiabetics as well as in albuminuric diabetics compared to nonalbuminuric patients with diabetes (p value <0.001). These 2 proteins were higher in patients with severely increased albuminuria compared to patients with moderately increased albuminuria, even after adjustment for other metabolic factors (all p < 0.01). Moreover, areas under the curve of NGAL and RBP-4 for the diagnosis of chronic kidney disease were 80.6 and 74.6%, respectively. Conclusion: uNGAL and RBP-4 are potential markers of tubular damage that may increase before the onset of glomerular markers such as albuminuria and GFR in patients with type 2 diabetes. Therefore, these markers can be used as complementary measurements to albuminuria and GFR in the earlier diagnosis of DN.